ANALISIS YURIDIS TERHADAP IMPLEMENTASI PEMBINAAN DAN PENGAWASAN NOTARIS OLEH MAJELIS PENGAWAS DAERAH TERKAIT NOTARIS YANG TIDAK MENJALANKAN JABATANNYA SECARA NYATA SETELAH DILANTIK DAN DISUMPAH (Studi MPD Binjai-Langkat) - MUHAMMAD RIZZA FUADY (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Suprayitno, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum A Notary is a public official who has the authority to draw up authentic deeds. In doing his job, he is coached and supervised by the Notarial Supervisory Council. A Notary who has been appointed and taken an oath is required to do his job seriously as it is stipulated in Article 7, paragraph 1 of UUJN (Notarial Act). He becomes the object of supervision by MPD. He becomes the object of supervision by MPD. The research problems are how about the role of MPD in coaching and supervising a Notary in the level of Districts/Towns, how about the implementation of MPD in coaching and supervising a Notary in Binjai-Langkat area, and how about the legal consequence of ay who violates his oath of under duress after he is appointed and taken an oath.Keywords: Implementation, Supervision, Regional Supervisory Council, Notary